THE INFLUENCE OF PARENTING PATTERNS ON ADOLESCENT BEHAVIOR AT SMA N 5 TELANAI PURA JAMBI CITY - Indra Saputra; Firman; A. Muri Yusuf (Literasi Nusantara, 2021)
Adolescent behavior is strongly influenced by parenting patterns. However, in reality, parents often forget their responsibilities. Therefore, this study aims to determine how big the contribution and influence of the parenting style variable in determining behavior in adolescents is. with a sample of 80 people, and then the data were collected through a questionnaire and analyzed by SPSS with simple linear regression analysis.